Insect Diversity in Taman Jangkar Surabaya - Nurul Aini; Ana Mariatul Khitiyah (AGARICUS: Advances Agriculture Science & Farming, 2022)
Insects are animals with jointed legs that are often found in many places with various types. This is because insects have a very high level of adaptation, for example those found in the Taman Jangkar in Surabaya. The purpose of this study was to describe the diversity of insects in the Taman Jangkararea and to compare the number of members of each insect order in the Taman Jangkar area. The method used in this research task is observation, which is to go directly to the field to capture insects around Taman Jangkar Surabaya with 4 repetitions in each plot, then collect data for identification. Based on the results of observations, collection, and identification, it can be obtained that there are various insects in the area. This is evidenced by the discovery of various orders of insecta, including: order Lepidoptera, order Odonata, order Hymenoptera, order Diptera, and order Orthoptera. Comparison of the number of species from each order is different. The most dominant number of species is in the order Lepidoptera which is then followed by the order Hymenoptera